Value Engineering: a promising tool to Oman Construction Sustainability - Al Amri, Tariq; Manuel Marey-Pérez (Technium Social Sciences Journal, 2021)
Oman is an oil-dependent state like other GCC states. In such regions, particularly Oman, the construction industry is booming and is currently the largest employer for the private sector’s Omani workforce. Moreover, Oman intends to diversify its economy to limit its dependency on oil to promote sustainability, as there is a possibility for future oil depletion. However, the thriving construction industries continue to score poorly in sustainability, raising the necessity for sustainability measures. Thus, this article proposes incorporating value engineering in the Omani construction sector to initiate sustainable measures for the industry. The article devised research questions elaborated using a systematic literature review to connect construction, sustainability, and quality aspects.